'Our periodic table of hate': The archive of 1984 Punjab in Jaspreet Singh's Helium. (2nd January 2018) - Sachdeva Mann, Harveen
ABSTRACT: Highly critical of the Indian government's cover up of the 1984 Sikh pogroms, Indian-Canadian author Jaspreet Singh offers a scathing expose of the anti-Sikh violence in his 2013 novel Helium . Singh experienced first-hand the 'holocaust' of 1984 in Delhi, and as a diasporic Indian since 1990, he is also intimately familiar with the burdens of postmemory among Sikhs in the west, many of whom sought asylum abroad in the wake of 1984. Influenced by Primo Levi and W.G. Sebald, Singh constructs a multi-generic 'archive' of the crimes of 1984 in Helium, which articulates the lingering trauma of the Sikhs and challenges the image of a unified, multiculturalist, secular-humanist postcolonial Indian state. Drawing on exhaustive research, Helium is a hybrid of fiction, survivor and relief worker testimonials, photographs, drawings, documentary, thriller, and inter-textual narrative—because the horror of 1984 cannot be recounted through a single medium or genre or voice. In considering its archival form and political intent, my article establishes Helium as a bold, ethical attempt to record the anti-Sikh violence of 1984 in order to bring justice to both the dead and the survivors.